Sosialisasi Perilaku Hidup Bersi dan Sehat (PHBS) untuk Mencegah ISPA dalam Peningkatan Pengetahuan pada Anak Sekolah Dasar Negeri 18 Dewantara, Kabupaten Aceh Utara - Dian Rahayu; Dhini Aminarti; Alya Salsabila Oktaviranda (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2026)
Acute Respiratory Infection (ARI) is one of the most common health problems among elementary school-aged children and contributes to a high morbidity rate. One of the contributing factors to ARI is the low implementation of Clean and Healthy Living Behavior (CHLB) as an early preventive measure. This community service activity was conducted at State Elementary School 18 Dewantara, Aceh Utara District, targeting 10 fifth-grade students. The method used in this activity was health education through interactive lectures and discussions, accompanied by a pre-test and post-test evaluation using questionnaires. The materials provided included the definition of ARI, risk factors, and the implementation of CHLB such as proper handwashing, personal hygiene maintenance, and correct coughing and sneezing etiquette. The results showed an increase in students’ knowledge after the educational session, with the average score rising from 78% to 88%, indicating an improvement of 10%. This demonstrates that the educational method used was effective in improving students’ understanding of ARI prevention. This activity is expected to foster clean and healthy habits among elementary school students and support promotive and preventive health efforts in the school environment.